ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PENYAJIAN LAPORAN KEUANGAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Kuswahyuning, Citra Cikita (Jurnal Riset Mahasiswa Akuntansi, 2014)
Timeliness is the communication of information early to avoid any delays or delays in making economic decisions. The financial statements must be presented in a timely manner in order to be relevant and available to the user and prior information in the financial statements lost its capacity to influence decisions. This study aims to analyze the factors that affect the timeliness of financial reports on banking companies listed in Indonesia Stock Exchange. The samples were banking companies listed in Indonesia Stock Exchange 2009-2012 period totaling 19 companies per year by using purposive sampling technique. The technique of collecting data is documentation. This type of research uses quantitative data banking companys financial statements listed in the Indonesia Stock Exchange Analysis using logistic regression analysis. Partial results of the study showed that financial leverage (DER) and profitability (ROA) significantly affects the timeliness of financial statement presentation. While firm size, firm age, and the quality of the KAP does not significantly influence the timeliness of financial statement presentation. The results of the study showed that simultaneous, financial leverage (DER), profitability (ROA), firm size, firm age, and the quality of the KAP significantly influence the timeliness of financial statement presentation. Desirable for future research to extend the study to increase the sample of all companies listed on the Indonesia Stock Exchange, adding a longer period of study and add to other factors that might impact on the timeliness of financial statement presentation.